Cardiopulmonary effects of dexmedetomidine and ketamine infusions with either propofol infusion or isoflurane for anesthesia in horses. (January 2015) - Duke-Novakovski, Tanya; Palacios-Jimenez, Carolina; Wetzel, Tara; Rymes, Lisa; Sanchez-Teran, Andres F
Abstract: Objective: To examine the cardiopulmonary effects of two anesthetic protocols for dorsally recumbent horses undergoing carpal arthroscopy. Study design: Prospective, randomized, crossover study. Animals: Six horses weighing 488.3 ± 29.1 kg. Methods: Horses were sedated with intravenous (IV) xylazine and pulmonary artery balloon and right atrial catheters inserted. More xylazine was administered prior to anesthetic induction with ketamine and propofol IV. Anesthesia was maintained for 60 minutes (or until surgery was complete) using either propofol IV infusion or isoflurane to effect. All horses were administered dexmedetomidine and ketamine infusions IV, and IV butorphanol. The endotracheal tube was attached to a large animal circle system and the lungs were ventilated with oxygen to maintain end-tidal CO2 40 ± 5 mmHg. Measurements of cardiac output, heart rate, pulmonary arterial and right atrial pressures, and body temperature were made under xylazine sedation. These, arterial and venous blood gas analyses were repeated 10, 30 and 60 minutes after induction. Systemic arterial blood pressures, expired and inspired gas concentrations were measured at 10, 20, 30, 40, 50 and 60 minutes after induction. Horses were recovered from anesthesia with IV romifidine. Times to extubation, sternal recumbency and standing were recorded. Data were analyzed using one and two-way anova s for repeated measures and paired t -tests. Significance was taken at p =0.05. Results: Pulmonary arterial and right atrial pressures, and body temperature decreased from pre-induction values in both groups. PaO2 and arterial pH were lower in propofol-anesthetized horses compared to isoflurane-anesthetized horses. The lowest PaO2 values (70–80 mmHg) occurred 10 minutes after induction in two propofol-anesthetized horses. Cardiac output decreased in isoflurane-anesthetized horses 10 minutes after induction. End-tidal isoflurane concentration ranged 0.5%–1.3%. Conclusion and clinical relevance: Both anesthetic protocols were suitable for arthroscopy. Administration of oxygen and ability to ventilate lungs is necessary for propofol-based anesthesia.